A case study of Waqf Institutions: reasons for not implementing crowdfunding / Nur Athirah Abd Rahman ... [et al.] - Abd Rahman, Nur Athirah; Abd Mutalib, Hasyeilla; Abdull Rahman, Nurul Labanihuda; Gzahli, Nurnazifa; Muhammad Rizal, Nur Ain Nazihah (Universiti Teknologi MARA, Perlis, 2024)
The crowdfunding industry in Malaysia has experienced rapid growth, with a variety of platform options available in the market. The increasing popularity of crowdfunding in Malaysia can be attributed to the support of information systems, particularly the internet and technology. The realm of financial technology innovations serves to enhance multiple facets of waqf fund management, particularly in addressing the challenges encountered by existing waqf models. As a result, waqf institutions can meet their liquidity needs for developing waqf properties without heavy reliance on government fund allocations by using the crowdfunding. Crowdfunding serves as a promising mechanism to achieve these objectives. Hence, the purpose of this study is to investigate why the waqf institution does not use crowdfunding to collect waqf funds. This study took a qualitative approach, analysing three chosen SIRCs in Malaysia's Northern Region. The data is subsequently subjected to thematic analysis. According to the survey, both WI1 and WI2 do not adopt crowdfunding owing to a lack of expertise and seek to increase the use of cashless waqf; however, WI3 already uses crowdfunding as a way of collecting waqf funds. The findings from this study will provide researchers with new information.